Location, morphology and function of nephrocytes in termites - Costa-Leonardo, Ana Maria [UNESP]; Janei, Vanelize [UNESP]; Laranjo, Lara Teixeira [UNESP]; Haifig, Ives [UNESP] (Elsevier B. V., 2015)
Insect nephrocytes are cells bathed in hemolymph and considered to have an excretory function. These cells have ambiguous nomenclature and are understudied in termites. This study is the first report on the occurrence, morphology and function of nephrocytes in different termite castes. Cytological characteristics in specific developmental stages and castes enable physiological functions to be inferred. Perforate diaphragms indicate a role in filtration, while the extensive peripheral invaginations of the cell membrane suggest active endocytosis. A sequence of morphologies in putative digestive vacuoles infers a lysosomal system and the occurrence of phosphatases suggests a function involving detoxification of substances sequestered from hemolymph. Pericardical nephrocytes took up the dye trypan blue injected in live termites, suggesting their activity connected to the filtration of the hemolymph. Additionally, histochemical tests showed the existence of stored proteins in their cytoplasm. These cells present a well-developed Golgi apparatus and abundant rough endoplasmic reticulum, consistent with protein synthesis. This study highlights the importance of nephrocytes in Isoptera and opens perspectives for further research of these cells.
Keywords: Athrocytes; Excretory system; Isoptera; Pericardial cells